Armazenamento de propágulos vegetativos usados como material de construção em intervenções de engenharia natural - Cadoná, Suelen Camargo (2014)
Soil bioengineering is a discipline of civil engineering that uses live elements as construction materials in order to produce technical effects, without neglecting aesthetic and ecological issues. Plant propagules are one of the most employed vegetative materials in different soil bioengineering schemes. These propagules are used to stabilize soil engineering properties by means of the posterior plant root development. Live material, consisting, in general, of wooden stakes and stem posts, could not be stored indefinitely, having a maximum or an optimal storage period before being implanted as construction material in soil bioengineering interventions. The objective of this work is to evaluate the most appropriate storage to preserve plant propagules (wooden cuttings) viability. Three species had been used for the study: Phyllanthus sellowianus, Salix humboldtiana and Sebastiania schottiana. Propagules of those three species are stored in three different wrap materials: Kraft paper, moist transparent polyethylene and dry transparent polyethylene. Each packed set is then preserved in two different temperature states (room temperature – unrefrigerated – and refrigerated environment at 8°C ± 2ºC). The vegetative viability of the material is verified by means of the success rate (IP) of the implanted sets, evaluated after different storage periods: reference sampling (non-stored), 3, 6, 9, 12, and 15 days. The live cuttings had their IP evaluated after 60 days of planting. The results show that the dry polyethylene storage produced the best preserving effects. Storage in Kraft paper, allowed moisture exchange between plant material and external environment. This fact leads to fast dehydration and death of the plant material. Moist polyethylene packing, meanwhile, creates conditions for the proliferation of fungi and bacteria, also reducing the vitality of the stored material. The results indicate that the storage of the studied species is feasible in dry polyethylene packing for up to 15 days (maximum tested period). The main refrigeration effects are: to decrease fungi and bacteria proliferation and to improve S. humboldtiana viability. S. schottiana success rate is significantly improved when it is stored by at least three days before planting The obtained results are useful as important information for planning and scheduling soil bioengineering works execution.